Injecting drug use in low and middle‐income countries: Opportunities to improve care and prevent harm. Issue 9 (1st August 2017) - O'Keefe, D.; Stoové, M.; Doyle, J.; Dietze, P.; Hellard, M.
Summary: Inadequate response to injecting drug use (IDU) is a significant problem the world over. Low levels of funding, political inaction, poor levels of health service coverage, high prevalence and incidence of IDU‐related blood‐borne viruses (BBVs) and ongoing stigmatization/marginalization affect people who inject drugs (PWID) regardless of the income status of the country they reside in. These barriers and system failings are, however, exacerbated in low and middle‐income countries (LMICs), meaning that the potential consequences of inaction are more pressing. In this narrative review, we describe the levels of IDU and IDU‐specific BBV prevalence in LMICs; levels of harm reduction implementation; the consequences of late or insufficient response, the shortcomings of data collection and dissemination; and the barriers to effective LMIC harm reduction implementation. We also exemplify cases where IDU‐related harms and BBV epidemics have been successfully curtailed in LMICs, showing that effective response, despite the barriers, is possible. In conclusion, we suggest four key priorities on the basis of the review: confirming the presence or absence of IDU in LMICs, improving the collection and dissemination of national IDU‐specific data, increasing the level of harm reduction programme implementation in LMICs, and increasing both national and international advocacy for PWID and attendant public health interventions.